The Effect of VR Avatar Embodiment on Improving Attitudes and Closeness Toward Immigrants - Chen, Vivian Hsueh Hua; Ibasco, Gabrielle C.; Leow, Vetra Jing Xuan; Lew, Juline Yun Yee (Frontiers in Psychology, 2021)
Past research has discussed how the embodiment of an outgroup avatar in virtual reality (VR) can reduce intergroup bias. However, little is known about the mechanisms and boundary conditions that shape this effect. This study examines how the embodiment of both outgroup and ingroup VR avatars in different orders influences attitudes and perceived closeness toward a co-ethnic immigrant outgroup in Singapore. It also investigates the role of empathy and social identity orientation in this relationship. An experiment with four avatar embodiment conditions (ingroup-then-outgroup, outgroup-then-ingroup, ingroup-only and outgroup-only) was carried out with 171 participants from a public university in Singapore. Results showed that embodying an outgroup avatar alone, compared to embodying an ingroup avatar alone, significantly improves both attitudes and closeness toward an immigrant outgroup. The order of embodiment matters to an extent, suggesting the greater effectiveness of outgroup-first over ingroup-first embodiment in reducing bias. Empathy mediates the effect of all three outgroup embodiment conditions on improved attitudes and closeness toward immigrants. It was also found that the stronger one’s social identity orientation is, the more effective embodiment is in improving perceived closeness with the outgroup via empathy. Theoretical implications of these findings are discussed.